2019
DOI: 10.3389/fvets.2019.00414
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Telemetric Assessment of Cardiac Variables and Locomotion With Experimentally Induced Hypermagnesemia in Horses Using Chronically Implanted Catheters

Abstract: The objective of this study was to characterize the pharmacokinetics and pharmacodynamics of intravenous administration of magnesium sulfate to horses using a novel radio-telemetry system for physiologic signal capture. Five Horses were surgically implanted with a radio-telemetric carotid catheter. Implants were paired with a non-invasive telemetric unit which acquired a six lead ECG and 3-axis acceleration to assess activity acquired wirelessly in real-time for future analysis. Horses were exposed to a new st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…It was also demonstrated that hypermagnesemia reduced headshaking behavior in horses [19]. These actions of Mg have been attributed to its ability to block N-methyl-D-aspartate (NMDA) ionotropic receptors and voltage-dependent calcium channels, reducing neuronal excitability [1,2,21,22]. The inhibitory effect of Mg 2+ over NMDA receptor activity has also been the rationale for its use in acute brain injury, nociception, anesthesia, and behavioral disorders [1][2][3]19,21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was also demonstrated that hypermagnesemia reduced headshaking behavior in horses [19]. These actions of Mg have been attributed to its ability to block N-methyl-D-aspartate (NMDA) ionotropic receptors and voltage-dependent calcium channels, reducing neuronal excitability [1,2,21,22]. The inhibitory effect of Mg 2+ over NMDA receptor activity has also been the rationale for its use in acute brain injury, nociception, anesthesia, and behavioral disorders [1][2][3]19,21].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical implications of short-term hypermagnesemia on behavior, cardiovascular function, and neuromuscular activity in horses were recently documented [2,3,19], further demonstrating that Mg is a pleiotropic ion. Magnesium supplementation is recommended for a number of human disorders and is being promoted as a pre-anesthetic to reduce pain [21].…”
Section: Plos Onementioning
confidence: 96%
See 3 more Smart Citations